The effect of fennel on the amount and duration of menstrual bleeding: A quasi-experimental study - Roya Motavalli; Samira Shahbazzadegan (Mashhad University of Medical Sciences, 2024)
Introduction: With the increasing use of medicinal plants in the treatment of some diseases, studying their side effects is very important. One of these herbal medicines is fennel that various results have been reported regarding its side-effects on the amount of menstrual bleeding, therefore, the present research was conducted with aim to investigate the effect of fennel on the amount and duration of menstrual bleeding. Methods: This quasi-experimental study was performed in 2016 on 50 students with primary dysmenorrhea living in the dormitories of Islamic Azad University, Ardabil. Participants were examined in three consecutive menstrual cycles. In the first cycle, participants did not take any medication; in the second and third cycles, in the first 3 days of menstruation they used fennel of 3-5 drops in water or tea three times a day. The standard Higham chart was used to determine the amount and duration of bleeding. Data was analyzed by SPSS software (version 17) and Paired-t test. P<0.05 was considered statistically significant. Results: The mean amount of bleeding before consuming fennel was 46.7±24.8 and in two consecutive cycles after consuming fennel were 48.4±26.2 and 49.5±24.3, respectively, which was not statistically significant. Moreover, no significant difference was observed in the duration of menstrual bleeding before the treatment (6.13±1.33) compared to two consecutive cycles after fennel consuming (6.82±1.45 and 6.26±1.02) (P>0.005). Conclusion: In the present study, fennel consumption had no effect on the amount and duration of menstrual bleeding. To determine the definitive result and the safety use of fennel, conducting more studies is recommended.